Diazotroph derived nitrogen supports diatom growth in the South West Pacific: A quantitative study using nanoSIMS. (1st July 2016) - Bonnet, Sophie; Berthelot, Hugo; Turk‐Kubo, Kendra; Cornet‐Barthaux, Véronique; Fawcett, Sarah; Berman‐Frank, Ilana; Barani, Aude; Grégori, Gérald; Dekaezemacker, Julien; Benavides, Mar; Capone, Douglas G.
Abstract: Nitrogen is essential for life but is often a major limiting nutrient for growth in the ocean. Biological dinitrogen fixation is a major source of new nitrogen to surface waters and promotes marine productivity. Yet the fate of diazotroph‐derived nitrogen (DDN) in marine ecosystems has been poorly studied, and its transfer to auto‐ and heterotrophic plankton has not been measured. Here, we use high‐resolution nanometer scale secondary ion mass spectrometry (nanoSIMS) coupled with 15 N2 isotopic labelling and flow cytometry cell sorting to examine the DDN transfer to specific groups of natural phytoplankton and bacteria during three diazotroph blooms dominated by the cyanobacterium Trichodesmium spp. in the South West Pacific. During these experiments, 13% ± 2% to 48% ± 5% of the fixed 15 N2 was released into the dissolved pool and 6% ± 1% to 8% ± 2% of this DDN was transferred to non‐diazotrophic plankton after 48 h. The primary beneficiaries of this DDN were diatoms (45% ± 4% to 61% ± 38%) and bacteria (22% ± 27% to 38% ± 12%), followed by pico‐phytoplankton (3% ± 1% to 21% ± 14%). The DDN was quickly converted to non‐diazotrophic plankton biomass, in particular that of diatoms, which increased in abundance by a factor of 1.4–15 over the course of the three experiments. The single‐cell approach we used enabled quantification of the actual transfer of DDN to specific groups of autotrophic and heterotrophic plankton in the surface ocean, revealing a previously unseen level of complexity in the pathways that occur between N2 fixation and the eventual export of DDN from the photic zone.